Changing state of gynecologic oncologist specialty in Japan. Issue 5 (14th March 2016) - Fujii, Takuma
Abstract: Gynecologic oncologists must have extensive knowledge regarding the methods of treating a diverse range of gynecologic cancers as well as the ability to perform cutting‐edge multidisciplinary treatments that frequently involve surgery. Given that coordination with other medical departments is vital for treatment, a high level of interpersonal and technical skills needs to be demonstrated to form the axis for medical treatment. One objective of the specialist certification system is the grooming of leaders as gynecologic oncologists while instructing trainees. The most distinguishing feature of Japanese gynecologic oncologists is that they need experience in more than 150 invasive cancer treatments, including more than 100 operations within the last 3–5 years. As for performance of surgery, at least 30 operations, including 15 radical hysterectomies, are required. Since surgical methods, including laparoscopic surgery, are undergoing a radical change, and increasing numbers of patients are undergoing radiotherapy for invasive cervical cancer, a review of the necessary requirements is critical. It is important to foster new leaders who are research‐oriented. Now is the time for marked reform with the new specialist certification system being introduced by the Japanese Medical Specialty Board. Japan has the advantage of offering medical services at a much lower cost because of its national health insurance system. However, specialists are currently not receiving clear benefits befitting their efforts, and the question of how to maintain their motivation is an issue for the future. For these purposes, I believe securing incentives is a critical issue for specialists.